Saudi Arabia : 2019 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
Reforms are starting to yield positive results. Oil prices and production have been volatile, and uncertainties in the global oil market continue. Promoting non-oil growth and creating jobs for Saudi nationals remain key challenges. Non-oil growth is expected to strengthen further this year and over the medium term. Risks to the growth outlook are broadly balanced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet